The land of stories world collide - Colfer, Chris (The land of stories, 2018)
The epic conclusion to Chris Colfer's No.1 New York Times bestselling series The Land of Stories! In the highly anticipated finale, Conner and Alex must brave the impossible. All of the Land of Stories fairy tale characters - heroes and villains - are no longer confined within their world! With mayhem brewing in the Big Apple, Conner and Alex will have to win their biggest battle yet. Can the twins restore order between the human and fairy-tale world? Breathtaking action mixed with laugh-out-loud moments and lots of heart will make this a gripping conclusion for fans old and new.